Comparative responsiveness of the health utilities index and the RAND-12 for multiple sclerosis. (October 2021) - Marrie, Ruth Ann; Leung, Stella; Cutter, Gary R; Fox, Robert J; Salter, Amber
Background: Outcome measures need to be valid and have good test–retest reliability and responsiveness. We compared the responsiveness of the RAND-12 and the Health Utilities Index—mark III (HUI3) in persons with multiple sclerosis (MS). Methods: In Spring 2018 and 2019, North American Research Committee on Multiple Sclerosis (NARCOMS) registry participants completed the HUI3, the RAND-12, and reported disability (Patient Determined Disease Steps (PDDS)) and employment status (full-time, part-time, and no). We used changes in PDDS and employment status as anchors. We assessed responsiveness using effect size, standardized response mean, and the responsiveness index. We used relative efficiency (RE) to compare the responsiveness of the health-related quality of life (HRQOL) scores, adjusting for sociodemographic factors. Results: We included 4769 participants in the analysis. They had a mean (standard deviation (SD)) age of 60.9 (10.1) years, and 3826 participants (80.2%) were women. RE was highest for the HUI3 for changes in in disability status (HUI3: 1.0, Physical Component Score-12 (PCS-12): 0.80, and Mental Component Score-12 (MCS-12): 0.41) and for changes in employment status (HUI3: 1.0, PCS-12: 0.70, and MCS-12: 0.17). Conclusion: The HUI3 was more responsive to changes in disability and employment status than the PCS-12 or MCS-12. Given the HUI3's other strong psychometric properties, it may be the preferred generic measure of HRQOL in MS.